2012
DOI: 10.1063/1.4704819
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of rare gas hydride cations: HRgN2+ (Rg=He, Ar, Kr, and Xe)

Abstract: Rare gas containing protonated nitrogen cations, HRgN(2)(+) (Rg=He, Ar, Kr, and Xe), have been predicted using quantum computational methods. HRgN(2)(+) ions exhibit linear structure (C(∞v) symmetry) at the minima and show planar structure (C(s) symmetry) at the transition state. The stability is determined by computing the energy differences between the predicted ions and its various unimolecular dissociation products. Analysis of energy diagram indicates that HXeN(2)(+) is thermodynamically stable with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 64 publications
0
25
2
Order By: Relevance
“…(The energy barriers for decomposition into NH 4 + and Ne are calculated to be 4.9 and less than 1 kJ mol −1 at the B3LYP and MP2 levels of theory, respectively.) For the He-, Ar-, Kr-, and Xe-derivatives, the HNgNH 3 + cation is higher in energy than the global minimum of NH 84 the energy barriers for the reaction HNgN 2 + → HN 2 + + Ng were calculated to be 2.3(6.2), 6.3(7.3), and 8.0(8.9) for Ng = He, Ar, and Kr at the B3LYP (CCSD(T)) levels of theory, respectively. Clearly, the HNgNH 3 + species possesses a higher stability than HNgN 2 + .…”
Section: B Stabilitymentioning
confidence: 96%
See 3 more Smart Citations
“…(The energy barriers for decomposition into NH 4 + and Ne are calculated to be 4.9 and less than 1 kJ mol −1 at the B3LYP and MP2 levels of theory, respectively.) For the He-, Ar-, Kr-, and Xe-derivatives, the HNgNH 3 + cation is higher in energy than the global minimum of NH 84 the energy barriers for the reaction HNgN 2 + → HN 2 + + Ng were calculated to be 2.3(6.2), 6.3(7.3), and 8.0(8.9) for Ng = He, Ar, and Kr at the B3LYP (CCSD(T)) levels of theory, respectively. Clearly, the HNgNH 3 + species possesses a higher stability than HNgN 2 + .…”
Section: B Stabilitymentioning
confidence: 96%
“…Phys. 142, 144301 ( 84 These values indicate relatively intense stretching vibrations of HNgNH 3 + (Ng = He, Ar, Kr, and Xe), which correspond to the chemical bonding species rather than weak van der Waals (vdW) complexes. .…”
Section: Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the synthesis and identification of rare gas compounds, a number of theoretical groups have reported studies on the stability, formation mechanisms, structure, and bonding nature of several rare gas compounds. [5,6,[25][26][27][28][29][30][31][32][33][34][35] We have reported that insertion of an Ng atom remarkably enhances the nonlinear response of the resulting derivative. [36] This has been attributed to the noteworthy lowering of the excited states accompanied by more intense allowed electronic transitions.…”
Section: Introductionmentioning
confidence: 99%